SOCIO-POLITICAL BLOGS IN MALAYSIA: CHALLENGES TO REGIME SECURITY - Ab Raman, Nurul Aishah; Sualman, Ismail (Journal of Techno-Social, 2016)
There are substantive scholarly works on blogs and its correlation to democratization using Jurgen Habermas public sphere concept, yet few ventures deep into the polity of Malaysia as multi-cultural, multi-ethnic nation. March 2008 general elections, marks the tipping point in Malaysia when it sees a steady rise of internet usage that have successfully denied the BN government for the first time its two-third majority. This research attempts to answer the reasons why socio-political blogs becomes the weapon of choice for public deliberations. The key issues explored are related to the four elements in the Constitution pertaining to the Malay supremacy which is the Malay rights, the monarchy, the Malay language and Islam as the official religion. The findings show that the regime does use these elements, in parts, to justify the suppression of political information and criticism, for maintaining national security and racial harmony while at the same time showcases digital acceptance to appease the demands of the public for a more democratic government.